γ-Valerolactone synthesis from α-angelica lactone and levulinic acid over biobased multifunctional nanohybrid catalysts - Antunes, Margarida M. (2022)
The selective chemical conversion of biomass components to useful bioproducts may contribute to a renewable resource-based economy. The selective production of target bioproducts may be accomplished using heterogeneous catalysts operating under relatively moderate reaction conditions. In this work, carbohydrate biomass derived α-angelica lactone (AnL) and levulinic acid (LA) were converted to the versatile bioproduct γ-valerolactone (GVL), in the presence of nanohybrid catalysts (M-FDCA) and the microcrystalline metal-organic framework CAU-28, all of which were synthesized from bio-based 2,5-furandicarboxylic acid (FDCA) and a metal (M = Zr or Hf) precursor. The nanohybrids were prepared in a simple fast (FT) fashion, and, for comparison, via a conventional solvothermal (S) procedure. The M-FDCA catalysts stood on a higher footing than AU-28 in the conversion of AnL and LA to GVL. The superior results for the M-FDCA catalysts may be partly due to their higher ratio Sext:SBET and nano-features, which may advantageously enhance active sites accessibility. In particular, the Hf-FDCA catalysts were stable and performed superiorly to the Zr-FDCA ones. Experimental mechanistic studies shed light on the multifunctional behavior of the hybrid catalysts in the one-pot conversion of AnL-to-GVL, which involved acid and reduction chemistry.